(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role, significance, and methodological features of empirical research in the process of scientific knowledge. The article highlights the role of empirical methods - observation, experimentation, questionnaires, and statistical analysis - in ensuring the reliability of scientific results. The relationship between empirical research and theoretical research, and the advantages of their combined use, are also discussed.